2021
DOI: 10.1101/2021.09.09.459560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metallothionein-2A protect Cardiomyocytes from Ischemia/Reperfusion through inhibiting p38

Abstract: The resumption of coronary artery blood supply is often accompanied by myocardial ischemia/reperfusion (I/R) injury after the occurrence of myocardial infarction, shock, cardiac surgery and other events. Metallothionein-2A (MT2A) has the functions of scavenging free radicals, anti-oxidative stress, anti-apoptosis, anti-autophagy, promoting vascular growth. The activation of p38 MAPK pathway can induce cardiomyocyte apoptosis in H9c2 cardiomyocytes during I/R, thereby aggravating the myocardial I/R injury. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…MT-induced inhibition of the NF-κB pathway has been linked to prevention of age-associated cardiomyopathy ( Cong et al, 2016 ). A recent study suggests that MT2A protects cardiomyocytes from I/R through p38 inhibition ( Zhao et al, 2021 Preprint ). It has also been shown that MT inhibits doxorubicin-induced mitochondrial cytochrome c release and caspase-3 activation in cardiomyocytes ( Wang et al, 2001 ).…”
Section: Dysregulation Of Cardiac Zn 2+ Homeostasi...mentioning
confidence: 99%
“…MT-induced inhibition of the NF-κB pathway has been linked to prevention of age-associated cardiomyopathy ( Cong et al, 2016 ). A recent study suggests that MT2A protects cardiomyocytes from I/R through p38 inhibition ( Zhao et al, 2021 Preprint ). It has also been shown that MT inhibits doxorubicin-induced mitochondrial cytochrome c release and caspase-3 activation in cardiomyocytes ( Wang et al, 2001 ).…”
Section: Dysregulation Of Cardiac Zn 2+ Homeostasi...mentioning
confidence: 99%